Outbreak of Cholera Due to Cyclone Kenneth in Northern Mozambique, 2019 - Cambaza, Edgar (Int J Environ Res Public Health, 2019)
Cyclone Kenneth was the strongest in the recorded history of the African continent. It landed in the Cabo Delgado province in northern Mozambique on 25 April 2019, causing 45 deaths, destroying approximately 40,000 houses, and leaving 374,000 people in need for assistance, most at risk of acquiring waterborne diseases such as cholera. This short article aims to explain how the resulting cholera outbreak occurred and the response by the government and partner organizations. The outbreak was declared on 2 May 2019, after 14 cases were recorded in Pemba city (11 cases) and the Mecúfi district (3 cases). The disease spread to Metuge, and by the 12th of May 2019, there were 149 cases. Aware of the risk of an outbreak of cholera, the government and partners took immediate action as the cyclone ended, adapting the Cholera Response Plan for Beira, revised after the experience with cyclone Idai (4–21 March 2019). The response relevant to cholera epidemics consisted of social mobilization campaigns for prevention, establishment of treatment centers and units, coordination to improve of water, sanitation and hygiene, and surveillance. By 26 May 2019, 252,448 people were immunized in the area affected by cyclone Kenneth. The recovery process is ongoing but the number of new cases has been reducing, seemingly due to an efficient response, support of several organizations and collaboration of the civil society. Future interventions shall follow the same model of response but the government of Mozambique shall keep a contingency fund to manage disasters such as cyclone Idai and Kenneth. The unlikeliness of two cyclones (Idai and Kenneth) within two months after decades without such kind of phenomena points towards the problem of climate change, and Mozambique needs to prepare effective, proven response plans to combat outbreaks of waterborne diseases due to cyclones.